(untitled) (REMUNOM, 2025)
This article focuses on the relationship between family and school in the interference in the academic development of children, since it is observed that the roles involving education are being reversed. Families tend to excessively give up the right to educate and transmit values to their children, often leaving the responsibility to the school, which does not hold this right completely, and some behaviors are the family’s obligation. Based on these precepts, this research aims to analyze how the relationship between family and school interferes in the academic performance of children. The methodology adopted is a qualitative bibliographic review and focuses on studies that discuss the theme of this research. In the results, it was possible to conclude that the relationship between family and school can significantly interfere in the academic development of children, and there are ways in which this relationship can impact, such as emotional support, effective communication, expectations and values, support for learning, development of skills and improvement of performance.